Social Media's Impact on Global Purchasing Decisions via Key Insights: Dampak Media Sosial terhadap Keputusan Pembelian Global melalui Wawasan Utama - Sakdiyah , Ni’matus; Fitriyah, Hadiah (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the influence of social media on purchase decisions, focusing on entertainment, trendiness, and electronic word of mouth (E-WOM), with follower count as an intervening variable. Conducted on followers of the